A short-run forecasting model of the United States economy - Fair, Ray C. (Lexington, Mass. : Heath Lexington Books, 1971)
This book describe a short-run forecasting model of the united states economy and that the model differ from most other econometric model
Includes bibliographical references.
oo 20/9/18
Loans
Keywords: United States